ЭШИТИШДА НУҚСОНИ БОР БОЛАЛАРНИНГ ИЖТИМОИЙ МУҲИТГА МОСЛАШИШИ - Тасбаева, Г. (SCIENCE and SOCIETY, 2016)
The article is devoted to the issues of work with the children with auditory defect. The author emphasizes that it is necessary to create good conditions for the children. In kinder gartens it‘s effective to conduct the correction work with the children with auditory defect and teaching a spoken language. The comfortable friendly atmosphere and use of merry games play a great role in the development of mental abilities.